Do environmental benefits matter? A choice experiment among house owners in Germany - Martin Achtnicht (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Residential buildings strongly contribute to global CO2 emissions due to the high energy demand for electricity and heating, particularly in industrialised countries. Within the EU, decentralised heat generation is of particular relevance for future climate policy, as its emissions are not covered by the EU ETS. We conducted a choice experiment concerning energy retrofits for existing houses in Germany. In the experiment, the approximately 400 sampled house owners could either choose a modern heating system or an improved thermal insulation for their home. We used standard and mixed logit specifications to analyse the choice data. We found environmental benefits to have a significant impact on choices of heating systems. However, they played no role in terms of insulation choices. Based on the estimated mixed logit model, we further obtained WTP measures for CO2 savings.
Keywords: C25; D12; Q40; Q51; 330; Choice experiment; CO2 emissions; Energy efficiency; Energy saving; Mixed logit; Residential buildings; Willingness to pay; Wohneigentum; Heizungsanlage; Bausanierung; Energiesparen; Entscheidung; Test; Willingness to pay; Deutschland